2019
DOI: 10.25122/jml-2019-1008
|View full text |Cite
|
Sign up to set email alerts
|

The Avant Rehabilitation Program and Cerebrolysin for Treatment of Post-Stroke Dysphagia: A Case Report

Abstract: Dysphagia is recorded in approximately a third of ischemic stroke patients and is associated with malnutrition, aspiration, and pneumonia. We report a case study that assessed dysphagia (GUSS, Gugging Swallowing Screen), paralysis (MRC, Medical Research Council), and disability (mRS, modified Rankin Scale) in the AVANT program (Austrian Vietnamese Advancement Neurorehabilitation Treatment) - a collaboration program between Vietnam and Austria to standardize and systemize neurorehabilitation after stroke practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It is believed that the MV patients have continuously used ventilators after the tracheal cut, and the patient's ventilation time has no effect on the occurrence of VAP [ 6 ]. Anai et al showed that the ventilator treatment after tracheal cutting did not only increase the probability of VAP in patients but also exacerbate the patient's condition, and it would like to cause the patient to die [ 7 ]. Aoyama et al, with tracheal intubation, showed the initial use of washthaki to clean the oral cavity, which can effectively prevent the occurrence of VAP caused by bacterial oral inflammation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is believed that the MV patients have continuously used ventilators after the tracheal cut, and the patient's ventilation time has no effect on the occurrence of VAP [ 6 ]. Anai et al showed that the ventilator treatment after tracheal cutting did not only increase the probability of VAP in patients but also exacerbate the patient's condition, and it would like to cause the patient to die [ 7 ]. Aoyama et al, with tracheal intubation, showed the initial use of washthaki to clean the oral cavity, which can effectively prevent the occurrence of VAP caused by bacterial oral inflammation.…”
Section: Literature Reviewmentioning
confidence: 99%